استجابة أنظمة التحكم الهجينة للطائرات بدون طيار تحت تأثير الحمولات المتغيرة والمعلقة لمسافات طويلة: دراسة نظرية ومحاكاة - جمال عبدالرحمن الطيف الصغير; إبراهيم رمضان حسين بن عياد; عزالدين علي محمد بن نصرات (Surman Journal of Science and Technology, 2026)
This research paper addresses the challenges of stability and control in Unmanned Aerial Vehicles (UAVs) transporting slung loads via long-span cables under the influence of continuous mass variation during long-range missions. The primary challenge lies in the complex dynamic interference resulting from the "pendulum effect" and the Slack/Taut phenomenon in the cable, in addition to parametric uncertainty caused by gradual mass depletion. The study aims to develop an innovative hybrid control system that integrates Proportional-Integral-Derivative (PID) control, Artificial Neural Networks (ANN) for disturbance estimation, and Genetic Algorithms (GA) for real-time optimization of control gains. Simulation results in a MATLAB/Simulink environment for a 10-km flight mission demonstrated the superiority of the proposed hybrid system, achieving a 40% reduction in the payload swing angle and a 15% decrease in energy consumption, while maintaining high trajectory tracking accuracy compared to conventional controllers. These results contribute to enhancing the efficiency and safety of aerial logistics and agricultural operations.